ANALISIS KINERJA KEUANGAN DAN TINGKAT KESEHATAN KOPERASI WANITA PATRA DI KOTA DUMAI - Hariz Nugrahi Manuhutu; Suarman '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to analyze the financial performance and the level of health of Women Cooperatives Patra, judging from the ratio of the financial year 2012-2016. The place of this research is carried out in a cooperative environment Women Patra in Dumai. This research starts from February until April 2017. As for the kind of this research is a descriptive quantitative and qualitative research, that describes the results of research in the form of financial report data related to financial performance against the cooperative. The data source of this research data is obtained from the report of the women's Cooperative Sysop Liability Patra in 2012 to 2016. As for the data collection techniques that are used by the method the study documentation. The results showed that the financial performance of the cooperative of women of good 2012-2016 year of Patra. This is due to the condition of the Solvency Ratio Liquidity Ratio, and Rentability Ratio where the Current Ratio has increased from year to year. And to the level of health cooperative of the year 2014-2016 quite healthy. This is due to the increased occurrence of 2014-2016 years, where Capital aspects, the quality of earning assets and management gets the highest value in the year 2016.Keywords: Financial performance, the level of health care cooperatives, Solvency Ratio,Liquidity Ratio and the ratio of earning ratios.